PENINGKATAN TANGGUNG JAWAB DAN HASIL BELAJAR KOGNITIF SISWA KELAS III SD MELALUI MODEL PEMBELAJARAN JIGSAW PADA MATA PELAJARAN PKN - Dwijayani, Rizki; Relmasira, Stefanus C.; Hardini, Agustina Tyas Arsi (KALAM CENDEKIA PGSD KEBUMEN, 2018)
AbstractThis study is a classroom action research. This study aims to determine the increase of responsibility and cognitive learning outcomes of students by using Jigsaw type cooperative learning model in class III SDN Mangunsari 07 Salatiga. The subject of this action study is the third grade students of SDn MAngunsari 07 Salatiga. The study was conducted in two cycles, each cycle consisting of planning, implementation and observation, and reflection. Data analytical technique used is comparative descriptive method by comparing hsil learn and student responsibility on pre cycle, cycle I and cycle II. The results of the research by the researchers found that the students' learning outcomes showed that Jigsaw type cooperative learning model can improve learning outcomes from pre cycle, cycle I and cycle II with an average of 60.04 to 65.25 and 75.50 respectively. In addition, jigsaw type co-operative learning can improve student's learning responsibilities. The students' pre-cycle responsibilities are 53% in the category of less and 47% in the good category, the 50% cyclus is very good, 30% in the good category and 20% in the bad category, 80% in very good category and 20% in either category on cycle II. Through the learning of the team of experts (jigsaw) students can be responsible for their own learning and also the learning of others, and students are directly involved with the material that has been obtained. The result of the research can be concluded that the application of jigsaw learning model can improve student's cognitive responsibility and learning outcomes.Keywords: Responsibility, Learning Outcomes, PKn, Jigsaw AbstrakPenelitian ini merupakan penelitian tindakan kelas. Penelitian ini bertujuan untuk mengetahui peningkatan tanggung jawab dan hasil belajar kognitif siswa dengan menggunakan model pembelajaran kooperatif tipe Jigsaw pada kelas III SDN Mangunsari 07 Salatiga. Subjek penelitian tindakan ini adalah siswa kelas III SDN Mangunsari 07 Salatiga. Penelitian ini dilaksanakan dalam dua siklus, tiap siklus terdiri atas tahapan perencanaan, pelaksanaan dan observasi, serta refleksi. Teknik analisis data yang digunakan adalah metode deskriptif komparatif dengan membandingkan hasil belajar dan tanggung jawab siswa pada pra siklus, siklus I dan siklus II. Hasil penelitian diperoleh hasil belajar siswa meangani peningkatan pada siklus I dan siklus II dengan rata-rata masing-masing 60,04 menjadi 65,25 dan 75,50. Selain itu pembelajaran kooperatif tipe jigsaw dapat meningkatkan tanggung jawab belajar siswa. Tanggung jawab siswa pada pra siklus adalah 53% dalam kategori kurang dan 47% dalam kategori baik, meningkat di siklus I menjadi 50% dalam kategori sangat baik, 30% dalam kategori baik dan 20% kategori kurang baik, 80% dalam kategori sangat baik dan 20% dalam kategori baik pada siklus II. Melalui pembelajaran tim ahli (jigsaw)siswa dapat bertanggu jawab terhadap pembelajaran sendiri dan juga pembelajaran orang lain, serta siswa terlibat secara langsung terhadap materi yang telah didapatkan. Berdasarkan hasil penelitian dapat disimpulkan bahwa penerapan model pembelajaran kooperatif tipe jigsaw dapat meningkatkan tanggung jawab dan hasil belajar kognitif siswa.Kata kunci: Tanggung Jawab, Hasil Belajar, PKn, Jigsaw